Visual attention and cognitive effects of facial anonymization in 360° videos - Wöhler, Leslie; Ikehata, Satoshi; Aizawa, Kiyoharu (Frontiers in Virtual Reality, 2025)
We analyze perceptual effects of facial anonymization in 360° videos to understand how different anonymization technologies affect the attention and cognition of viewers. 360° videos provide highly immersive viewing experiences, making them ideal for the exploration of real world scenes. As videos of public locations generally include bystanders, it is necessary to apply facial anonymization to protect their privacy. However, this changes the visual content and might affect the attention and cognition of viewers. To investigate these effects, we perform an experiment in which participants watch 360° videos while we collect their eye tracking data. Additionally, we prepare questionnaires measuring presence, video quality, and memory of participants. Our results show differences in visual attention and the perceived video quality between anonymization techniques highlighting that it is important to consider the chosen facial anonymization technique.